Computing topological indices of chemical structures of the conductive 2D MOFs. Issue 3 (3rd April 2021) - Ahmad, Ali; Nadeem, Muhammad Faisal; Elahi, Kashif; Hasni, Roslan
Abstract: Degree based topological indices of chemical structures of the conductive 2D MOFs Cu 3 ( HITP )2 [ m, n ] are studied. Expressions for multiple Zagreb indices and Zagreb polynomials for these consequential classes of networks are obtained.